XYLANASE, AN ENVIRONMENTALLY FRIENDLY BLEACHING AGENT FOR PULP AND PAPER: CHARACTERIZATION AND STABILIZATION STUDY OF BACILLUS LICHENIFORMIS I-5 CRUDE XYLANASE - Wahyuntari., dkk, Budiasih (BPPT)
Isolate I-5 was isolated from Ciseeng hot spring, West Java and was identified as Bacillus licheniformis I-5. The isolate produces extracellular xylanolytic enzymes on Oatspelt containing Luria broth agar medium. Optimal activity of the crude enzyme was observed at 50ºC and pH 7. The effect of sodium dodecyl sulphate, b-mercaptoethanol and Triton-X100 were observed. Incubating the crude enzyme in 1.5% SDS and 1.5% b-mercaptoethanol at 50oC for 90 minutes then adding Triton-X100 at final concentration of 3.5% for 45 minutes only reduced 5.75% of the initial enzyme activity. SDS/PAGE and zymogram analysis showed that at least two xylanolytic enzymes presence in the crude enzyme. The molecular weight of the enzyme was estimated about 127 and 20kD. The enzyme hydrolysed xylan into xylobiose, xylotriose and other longer xylooligosaccharides. Thermal stability of the crude enzyme was observed at 50, 60, and 70oC and pH 7 and 8. The results showed that the half time of the crude enzyme incubated at 50, 60, and 70oC pH 7 was 2 hours 55 minutes; 2 hours 33 minutes and 1 hour 15 minutes respectively. The half time at 50, 60 and 70oC, pH 8 was 2 hours 48 minutes; 1 hour 22 minutes and 1 hour 9 minutes respectively.keywords: Xilanase, Bacillus licheniformis I-5, thermal stability